«ШӘРЬЯР» ДӘСТАНЫНДАҒЫ ГҮЛШАРА ОБРАЗЫ ЖАСАЛЫЎЫНЫҢ ГЕЙПАРА МӘСЕЛЕЛЕРИ - Кеңесбаева, Ш. (FAN va JAMIYAT, 2019)
The article deals with the issues of women’s characters in the epos «Shariyar» where Gulshara is main heroine. The author describes and analyzes the image of Gulshara. In the result of the analysis there have been defined some mythical-fantastic elements of this character. Gulshara is a realistic image that reflects the national peculiarities of Karakalpak women.